(untitled) (Journal of Enam Medical College, 2020)
Galactosemia is an autosomal recessive inheritance and there is cellular deficiency of enzymes leading to defective/impaired metabolism of galactose resulting in toxic byproducts like galactilol, galactose-1-phosphate and galactonate that affect mainly liver, brain, kidneys, lens and gonads. Galactosemia appears as a rare metabolic cause of neonatal cholestasis syndrome (NCS). The classic disease manifestation after the first milk feeding varies in severity from an acute fulminant illness to a more common subacute illness beginning within the first few days of life. Neonatal sepsis is one of the presentations. Galactokinase deficiency results primarily in cataract formation and galactosuria. The preliminary diagnosis of galactosemia in sick neonates and suspected infants is made by Benedict test in several urine specimens and followed by dipstick test to exclude glycosuria. Gold standard test is demonstration of low enzyme activity in erythrocyte. Galactosemia can be detected by newborn screening methods like the Guthrie test using filterpaper blood samples. Classical form of galactosemia should be treated with an absolute galactose restricted diet without waiting for confirmation of the diagnosis. Here we report a case of a 50-dayold boy with features of neonatal cholestasis, diagnosed as galactosemia by using a simple cost effective method. J Enam Med Col 2020; 10(1): 43-48